Pengaruh Gaya Hidup Berbelanja Dan Perilaku Hedonik Terhadap Pembelian Impulsif (Studi) Pada Toko Belanja Online Shopee - Debora Dian Maydiana Anggreani; Sentot Suciarto A. (JEMAP, 2020)
This research aimed to test the effect of shopping lifestyle and hedonic behavior toward impulsive buying. Population researched here are students consuming shopee online shopping with sampel 100 taken by purposive sampling. It was obtained test result that respon toward shopping lifestyle was agree, average score 4.18. Average respon toward hedonic behavior was agree, 3.87. Average respon toward impulsive buying was agree, namely 3.92. Based on regression analysis, shopping lifestyle positively and significantly effected impulsive buying. Hedonic behavior also effected toward impulsive buying. The test result  shopping lifestyle and hedonic behavior together significantly effected toward impulsive buying.